Experimental and Numerical Investigation of the Effect of Process Conditions on Residual Wall Thickness and Cooling and Surface Characteristics of Water-Assisted Injection Molded Hollow Products - Hyungpil Park; Baeg-Soon Cha; Byungohk Rhee (Advances in Materials Science and Engineering)
Recently, water-assisted injection molding was employed in the automobile industry to manufacture three-dimensional hollow tube-type products with functionalities. However, process optimization is difficult in the case of water-assisted injection molding because of the various rheological interactions between the injected water and the polymer. In this study, the boiling phenomenon that occurs because of the high melt temperature when injecting water and the molding characteristics of the hollow section during the water-assisted injection process were analyzed by a water-assisted injection molding analysis. In addition, the changes in the residual wall thickness accompanying changes in the process conditions were compared with the analysis results by considering water-assisted injection molding based on gas-assisted injection molding. Furthermore, by comparing the cooling characteristics and inner wall surface qualities corresponding to the formation of the hollow section by gas and water injections, a water-assisted injection molding technique was proposed for manufacturing hollow products with functionality.